Radiotherapy with Neoadjuvant Chemotherapy on Nasopharyngeal Carcinoma (NPC) Advanced Stage - Robertus Suryoseto (TALENTA PUBLISHER, 2021)
Introduction: Nasopharyngeal carcinoma (NPC) frequently occurs in Indonesia which is endemic to several countries of Asia, specifically in southeastern China, and is associated of infection with Epstein-bar virus (EBV). In recovery, radiation therapy plays a vital role. Chemotherapy will increase the local control rate/disease control rate (DCR) in cases with an advanced local stage. Case report: A 49-year-old man felt a lump in his neck accompanied by ringing in his ears and sore throat. Physical examination showed a tumor in the right nasopharynx enlarged into the parapharynx cavity and closed Rosenmuller's fossa. The results of the biopsy were positive for non-keratinized, undifferentiated (WHO-3) type A nasopharyngeal carcinoma (NPC), moderate malignancy. The planned treatment consists of a combination of chemotherapy and radiotherapy. Chemotherapy is given 3 cycles before radiotherapy (neo adjuvant) and 3 cycles of concurrent radiotherapy (adjuvant). The total dose of radiotherapy given was 6,600 c Gy and supra clavicle 5,400 c Gy with fractionation of 33 times in the tumor and 27 times in the supra clavicle. Conclusion: The results presented 6 months after radiotherapy were complete response to loco regional tumors with well tolerated side effects.